Effect of holding temperature on isolation of Neisseria gonorrhoeae. - Evans, K D (1986)
The effect of holding temperature on the recovery of Neisseria gonorrhoeae was studied. From 300 specimens tested, Thayer-Martin medium plates inoculated and incubated in the presence of CO2 at 35, 22, and 4 degrees C for 24 h before incubation at 35 degrees C yielded 100, 96, and 95% of all isolates ultimately recovered from 82 positive specimens. Although there was a decrease in the quantity of organisms recovered, initial incubation of specimens under refrigeration or at room temperature yielded greater than or equal to 95% of the positive specimens.